Investigation on Spectroscopic and Laser Properties of Pyrromethene and Perylene Chromophores in Elastic Polymeric Hosts. Issue 20 (22nd October 2019) - Lin, Wenxin; Gong, Jianqiu; Zhou, Huizhong; Wang, Yijia; Gao, Linhui; Zhu, Hongliang; Chen, Jianjun
Abstract : In this work, two types of chromophore i.e. the pyrromethene and perylene families dyes were doped into elastic polymeric host materials based on polydimethylsiloxane (PDMS), which had been widely employed in various applications. The solubilities, spectroscopic and laser properties of these dyes doped into PDMS matrices were systematically investigated. Tunable laser output with high conversion efficiencies and low laser thresholds were observed and calculated. The laser longevity of pyrromethene dyes doped in PDMS matrices could exceed 1 × 10 5 pulses through a fast self‐recovery on the laser output with the elapse of aging time. The efficient and stable laser output of the dopants and the flexibility of the PDMS host provided the feasibility of such gain media as mechanically tunable laser sources, which might be employed as cost‐effective components on integrated bio‐chips. Abstract :